VD_FINDINFO 147/2009/JKR vom 2. Oktober 2009 - VD Tribunal cantonal (2009)
CONTRAT D'OUVERTURE DE CRÉDIT, NOVATION, COMPTE COURANT, CÉDULE HYPOTHÉCAIRE, ORGANE DE FAIT | 27 CC, 102 CO, 104 CO, 117 al. 2 CO, 144 CO, 19 CO, 21 CO, 318 CO